Day 2 Thu, September 15, 2016 2016
DOI: 10.2118/180299-ms
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Influence of ESP on Wellbore Temperature, Pressure, Annular Pressure Buildup, and Wellbore Integrity

Abstract: The electrical submersible pump’s (ESP) impact on wellbore temperatures and integrity is seldom discussed in literature. Most literature discusses ESP run life and failure. The ESP heat dissipation increases the wellbore temperatures. Therefore, direct and indirect thermal-induced stresses are applied to the casings and tubing. At the same time, the trapped annular pressure buildup (APB) also increases, thereby applying additional stress on the casings and tubing. This raises the question—is the safety factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In combination with electric heating technology, the amount of light oil can be reduced. In order to investigate whether the heat dissipation of the electric submersible pump has an impact on the stability of the wellbore, [14] modeled the transient wellbore temperature with full consideration of the heat dissipation of the electric submersible pump motor, pump, and cable. The calculation results of the model were compared with the measurement results of the field sensors, and the results showed that the model has good accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with electric heating technology, the amount of light oil can be reduced. In order to investigate whether the heat dissipation of the electric submersible pump has an impact on the stability of the wellbore, [14] modeled the transient wellbore temperature with full consideration of the heat dissipation of the electric submersible pump motor, pump, and cable. The calculation results of the model were compared with the measurement results of the field sensors, and the results showed that the model has good accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies [6][7][8][9][10][11][12][13][14][15] have addressed the problem of finding technical solutions to reduce gas pressure in the annular space at various methods of well operation. A review Energies 2022, 15, 5045 2 of 13 in [16] illustrates tools to reduce the impact of gas on the operation of downhole sucker-rod pumps and their effectiveness under various operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient liquid level above the pump leads to significant complications in the operation of well pumping units and reduces their efficiency [8]. In [9] the influence of gas on parameters of submersible centrifugal pumps was shown. In order to operate wells with high gas-oil ratio, it was necessary to develop multiphase rod downhole pump [10].…”
mentioning
confidence: 99%